Metastatic organotropism: a brief overview - Carrolo, Margarida; Miranda, João A. I.; Vilhais, Guilherme; Quintela, António; Sousa, Mário Fontes e; Costa, Diogo Alpuim; Pinto, Francisco R. (Frontiers in Oncology, 2024)
Organotropism has been known since 1889, yet this vital component of metastasis has predominantly stayed elusive. This mini-review gives an overview of the current understanding of the underlying mechanisms of organotropism and metastases development by focusing on the formation of the pre-metastatic niche, immune defenses against metastases, and genomic alterations associated with organotropism. The particular case of brain metastases is also addressed, as well as the impact of organotropism in cancer therapy. The limited comprehension of the factors behind organotropism underscores the necessity for efficient strategies and treatments to manage metastases.